Penerapan Asas Kepentingan Umum dalam Pengadaan Tanah untuk Pembangunan Infrastruktur Desa di Indonesia - Sinta Meilany Putri (Universitas Kuningan, 2025)
Village infrastructure development plays a crucial role in improving community welfare, yet it often faces obstacles in the land acquisition process. This study aims to analyze the application of the public interest principle in land acquisition through a case study in Wadas Village, Central Java. The method used was a desk study, reviewing relevant laws and regulations and literature. The study results indicate that although land acquisition is legally regulated, its implementation still generates conflict due to a lack of public participation and information transparency. The case in Wadas Village reflects community resistance to development projects due to concerns about environmental and social impacts. In conclusion, the application of the public interest principle must prioritize justice, transparency, and participation so that development does not compromise community rights.